TRANSLATING ECONOMICS TEXTBOOKS: A CASE STUDY OF EPISTEMICIDE - Karnedi, Karnedi (TEFLIN Journal, 2015)
As part of discourse in the social sciences, economics textbooks written in English in which knowledge has been transferred to other languages through translation have brought a certain impact on both the target language and the target culture. In terms of ideology, this article argues about the hegemonic status of the dominant language or culture that creates socalled epistemicide or the erosion of knowledge, partly due to translation strategies adopted by the translator. Investigation is done using the corpusbased approach, theories of translation strategies and the comparative model. The study reveals that the translator in the macro-level text adopts the ideology of foreignising strategy rather than domesticating strategy when translating an economics textbook from English into Indonesian. This is supported by the use of the number of the source language-orientated translation techniques leading to two translation methods (i.e. literal translation and faithful translation) adopted in the micro-level text. This research strongly supports another relevant study pertaining to the globalisation of knowledge through translation and also the translation theories of equivalence (i.e. overt and covert translation). The research findings also have some pedagogical implications on teaching English for Specific Purposes in higher education.